Quantitative analysis in a heuristic evaluation of web-based encyclopedia for children - Gita Indah Marthasari; Nur Hayatin (Universitas Ahmad Dahlan, 2021)
Anapedia is a web-based encyclopedia designed specifically for children. The web was built because there are still very few Indonesian-language encyclopedias for children. This paper presents an evaluation of the usability of the Anapedia website developed for children in Indonesia to retrieve information available in a wide range of areas. In the context of usability evaluation of children encyclopedia, this is the first study to analyze usability problems identified by experts during the heuristic inspection on their overall evaluation score. This evaluation, performed by seven usability experts, involved the identification and analysis of usability problems in the selected website. The assessment process was mainly based on the Sirius framework evaluation mechanism. The web considered as having high usability level, but they identified many usability problems for further improvement of the site. The most violated heuristic item was found to be “help” whereas the least violated heuristic item was “labelling” aspect.